A 10-year record of the isotopic composition of precipitation at Concordia station, East Antarctica - DREOSSI G; STENNI B; MASIOL M; SCARCHILLI C; CIARDINI V; DEL GUASTA M; PETTENI A; CASADO M; WERNER M; CAUQUOIN A; BARBANTE C (INQUARoma2023, 2023)
The atmospheric dynamics determining the isotopic composition of precipitation on the Antarctic Plateau are still under investigation. At Concordia station, East Antarctica, daily precipitation has been continuously collected on raised surfaces (height: 1 m) placed in a clean area, about 800 m from the station. Samples have been analyzed for δ18O, δD, and deuterium excess (d). The on-going monitoring of precipitation isotopic composition represents a unique record in inland Antarctica. Surface temperature (T2m) from the Dome C Automatic Weather Station of the Italian National Antarctic Research Program (PNRA) was correlated with isotopic data of precipitation collected from 2008 to 2017, in order to better understand the relationship between local temperature and the isotopic signal of precipitation. A robust positive correlation between δ18O and δD of precipitation and T2m is observed when using both daily and monthly-averaged data. δ18O and δD of precipitation were also compared to the simulation from the isotope-enabled atmospheric general circulation models ECHAM5-wiso and ECHAM6-wiso, with the most recent version showing a significant improvement.